THE INFLUENCE OF TAX PLANNING, PROFITABILITY, AUDIT COMMITTEE AND MANAGERIAL OWNERSHIP ON PROFIT MANAGEMENT - Sarti Hutabarat; Ester Novalina Saragih; Jesika Rejeki Br Siregar; Enda Noviyanti Simorangkir; Fhikry Ahmad Halomoan Siregar (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The aim of this research is to examine the role of earnings management in the success or failure of manufacturing industry trading on the Indonesia Stock Exchange (IDX) in various industry classifications. Fifty five businesses make up the population of this study. Purposive sampling was used to collect information about 39 businesses, of which 13 were selected as samples. Earnings management is the dependent variable, while tax planning, profitability, existence of an audit committee, and managerial ownership are independent variables. The data used in this research comes from the annual financial reports of producers registered through the Indonesia Stock Exchange in several industries from 2019 to 2021. The quantitative analysis approach used here tests conventional assumptions. Referring to the findings, profit management is not too affected by tax planning , audit committee membership, or managerial ownership. Earnings management is greatly affected by profitability. Profit Management of Manufacturing Companies Registered through the Indonesia Stock Exchange Year 2019-2021 Highly Affected by Tax Planning, Profitability, Audit Committee, and Managerial Ownership